Transparent and flexible high-performance supercapacitors based on single-walled carbon nanotube films. (28th April 2016) - Kanninen, Petri; Luong, Nguyen Dang; Sinh, Le Hoang; Anoshkin, Ilya V; Tsapenko, Alexey; Seppälä, Jukka; Nasibulin, Albert G; Kallio, Tanja
Abstract: Transparent and flexible energy storage devices have garnered great interest due to their suitability for display, sensor and photovoltaic applications. In this paper, we report the application of aerosol synthesized and dry deposited single-walled carbon nanotube (SWCNT) thin films as electrodes for an electrochemical double-layer capacitor (EDLC). SWCNT films exhibit extremely large specific capacitance (178 F g −1 or 552 μ F cm −2 ), high optical transparency (92%) and stability for 10 000 charge/discharge cycles. A transparent and flexible EDLC prototype is constructed with a polyethylene casing and a gel electrolyte.